Cement-based repair material based on ns modified pp fibers and use thereof

CN122958115APending Publication Date: 2026-10-23JIANGSU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611369482.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-04
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0004]然而,古建筑砖石基体孔隙率高、吸水性强且材质差异大,对修复材料的粘结性、耐久性、透气性和相容性要求较高

Benefits of technology

1、本发明通过引入NS改性PP复合材料,提高了水泥材料的抗裂性、抗疲劳性能,特别适用于修复地震导致产生的裂缝。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958115A_ABST
    Figure CN122958115A_ABST
Patent Text Reader

Abstract

The application discloses a cement-based repairing material based on NS modified PP fibers and application thereof. The cement-based material is used as a main body, polypropylene fibers are pretreated on the surface through a silane coupling agent, and the PP fibers are surface modified by using an NS solution, so that the NS is uniformly attached to the surface of the fibers, and the interface bonding performance between the polypropylene fibers and the cement matrix is improved. The modified PP fibers are added into the cement slurry in a wet pre-dispersion mode, so as to reduce fiber agglomeration and improve material uniformity. During construction, the crack part is cleaned with low damage, the interface is brushed with cement slurry, small-flow injection and layered filling and pressing repair are performed, and surface antique processing is performed after the repair is completed. The repairing material has good crack resistance, fatigue resistance, interface compatibility and construction adaptability, can reduce the secondary damage risk caused by the brittleness and poor interface combination of traditional repairing materials, and is suitable for repairing and protecting cracks of masonry structures of ancient buildings after the action of an earthquake.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of materials for the protection of cultural relics and buildings, and more particularly to a cement-based repair material based on NS-modified PP fibers, used for the repair of earthquake-damaged cracks in ancient buildings (such as brick and stone structures). A special construction method is employed to minimize damage to the existing materials of the ancient building. Background Technology

[0002] Ancient buildings are mostly constructed of brick and stone, and their structural performance has generally deteriorated due to long-term natural erosion and repeated earthquakes. These brick and stone structures are characterized by material aging, low strength, high porosity, and a high risk of irreversible damage. Earthquakes often cause cracks, surface peeling, loosening of masonry, and even partial collapse in these structures. After an earthquake, cracks not only affect structural safety but also accelerate the entry of rainwater, salt, and pollutants. Traditional repair and reinforcement methods mainly include cement mortar masonry, steel mesh reinforcement, pressure grouting, and epoxy resin grouting. However, cement-based materials are often heavy, brittle, and have significantly different physical and mechanical properties and coefficients of thermal expansion compared to the original brick and stone materials, making them prone to stress concentration and secondary damage over long-term use. While organic polymer materials such as epoxy resin have strong adhesion, they suffer from insufficient aging resistance, poor air permeability, large curing shrinkage, and poor compatibility with brick and stone. Furthermore, some materials are irreversible, which is detrimental to the principle of remanufacturability in cultural relic preservation.

[0003] In recent years, polymer-modified cement-based composites and high-performance polymers have received widespread attention in the field of structural repair. Polypropylene (PP), as a common polyolefin polymer, has advantages such as light weight, chemical resistance, and low cost; however, its interfacial adhesion with inorganic materials, its mechanical strength, and its anti-aging properties need improvement. Nano-silicon dioxide (NS), as a common inorganic nanomaterial, has characteristics such as small particle size, large specific surface area, and high surface activity. It can effectively fill microscopic defects in materials and improve the mechanical properties, thermal stability, and bonding force with inorganic interfaces of polymer matrices. Applying NS to modify PP is expected to significantly improve the overall performance of composite materials, making them more suitable for the repair of ancient brick and stone structures.

[0004] However, the brick and stone matrix of ancient buildings has high porosity, strong water absorption, and significant material differences, placing high demands on the adhesion, durability, breathability, and compatibility of restoration materials. Existing NS-modified PP materials still suffer from problems such as uneven NS adhesion, easy agglomeration, and insufficient fiber dispersion, resulting in limited improvement in interfacial adhesion. Furthermore, they may crack and peel under wet-dry cycles, temperature changes, or repeated loading, making it difficult to meet the long-term restoration requirements of ancient buildings.

[0005] Therefore, there is a need to develop a high-performance, highly adaptable restoration material that has significant engineering application value and cultural heritage protection significance. Summary of the Invention

[0006] To address the problems existing in current technologies, this invention provides a cement-based repair material based on NS-modified PP fibers and its application in structural crack repair. This method involves adding NS-modified PP composite materials and applying different construction methods specifically for the repair of ancient buildings. It can effectively repair structural cracks in ancient buildings, especially cracks in brick and stone structures, improving structural durability and reducing damage to structures from natural disasters such as earthquakes.

[0007] The technical solution of the present invention is as follows: A method for preparing a cement-based repair material based on NS-modified PP fiber includes the following steps: Step 1: Pre-treat the PP fibers to remove surface impurities; Step 2: Pre-treat the NS to obtain an NS dispersion with a mass fraction of 8% to 12%; Step 3: Prepare the silane coupling agent treatment solution; Step 4: Place the pretreated PP fiber in a silane coupling agent treatment solution to modify the surface of the PP fiber to be hydrophilic. Step 5: Add the hydrophilically modified PP fibers to the NS dispersion to make the NS evenly adhere to the surface of the PP fibers. Step 6: Obtain NS-modified PP fibers by low-temperature drying.

[0008] Step 7: Add NS modified PP fiber to water containing polycarboxylate superplasticizer at a volume dosage of 0.5 vol% to achieve wet pre-dispersion and obtain a uniformly dispersed fiber pre-dispersion slurry. Step 8: Add the fiber pre-dispersed slurry to the cement material to obtain NS modified PP fiber cement-based repair material for repairing cracks in masonry structures.

[0009] Furthermore, in step 1, the PP fiber is placed in deionized water for ultrasonic cleaning to remove floating dust, oil and other impurities from the surface of the PP fiber.

[0010] Further, an NS dispersion was prepared: NS was added to deionized water, and a polycarboxylate superplasticizer was added as a dispersant, wherein the amount of the polycarboxylate superplasticizer was 0.5% of the solution mass; the NS was uniformly dispersed in water by ultrasonic dispersion.

[0011] Further, silane coupling agent KH-550 is added to a mixed solution of deionized water and ethanol, and the pH of the solution is adjusted to 4.5-5.5 using glacial acetic acid; the amount of silane coupling agent added is 1% of the solution mass; the mixture is stirred continuously at room temperature for 30-60 minutes to allow the silane coupling agent to be fully hydrolyzed, resulting in a silane coupling agent treated solution.

[0012] Furthermore, the NS dispersion and PP fiber are prepared at a mass ratio of 5:1, and ultrasonic dispersion and physical stirring are used to make the NS uniformly adhere to the surface of the PP fiber, thus obtaining NS modified PP fiber.

[0013] Furthermore, the NS-modified PP fibers are dried at a low temperature of 50-80℃.

[0014] The application of a cement-based repair material based on NS-modified PP fiber in the repair of cracks in ancient building brick and stone structures, with the specific construction steps as follows: S1. Clean the dust from the cracked area; S2. Wet the surface and inner wall of the crack, and then apply a layer of cement slurry with the same ratio as the repair material as the interface bonding layer. S3. After the interface bonding layer has initially adhered, slowly inject the NS modified PP fiber cement-based repair material into the crack. S4. After the crack is filled, the surface of the repaired area is lightly smoothed. S5. After the material to be repaired reaches a preliminary hardening state, perform an antique-style surface treatment on the repair surface. S6. Perform maintenance on the repaired area.

[0015] Furthermore, during injection, start from the deeper or lower part of the crack and gradually advance towards the outside or upper part to ensure that the repair material fully fills the crack gaps.

[0016] Furthermore, a layered filling method is adopted, that is, after each layer of repair material is filled, it is compacted; after the previous layer has initially stabilized, the next layer is filled.

[0017] Compared with the prior art, the present invention has the following advantages: 1. This invention improves the crack resistance and fatigue resistance of cement materials by introducing NS-modified PP composite materials, making it particularly suitable for repairing cracks caused by earthquakes.

[0018] 2. This invention ensures that the treatment of cement materials maintains performance while being economical by comparing the amount of NS-modified PP composite material incorporated.

[0019] 3. By employing special processes to treat and modify NS and PP, and using silane coupling agent solutions to increase the surface affinity of PP fibers, the two materials can be better bonded together.

[0020] 4. The method of the present invention can not only improve the long-term performance of cement materials, but also has wide applicability, especially in the field of repairing cracks in ancient brick and stone structures in high-risk earthquake areas, where it can provide better repair results.

[0021] 5. The construction method of this invention increases the bonding between new and old materials while avoiding secondary damage to the old materials. Attached Figure Description

[0022] Figure 1 Schematic diagram of the microstructure of NS-modified PP fiber cement-based repair material.

[0023] Figure 2 Comparison of tensile stress-strain lines between ordinary CSH and CSH / PPNS composite systems.

[0024] Figure 3 Comparison of hysteresis curves under cyclic loading between ordinary CSH and CSH / PPNS composite systems.

[0025] Figure 4 Flowchart for the repair of cracks in the brick and stone structure of ancient buildings.

[0026] The attached figures are labeled as follows: 1. CSH matrix, 2. PP fiber, 3. NS cluster. Detailed Implementation

[0027] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0028] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0029] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be obvious to those skilled in the art. This application specification and embodiments are merely exemplary.

[0030] The following is in conjunction with the appendix Figures 1 to 4Specific embodiments of the present invention are described below. In the simulation, calcium silicate hydrate (CSH) was used as the main material, with natural sodium sulfate (NS) and polypropylene (PP) fibers introduced into it. The PP fibers initially bond with NS primarily through hydrogen bonds and van der Waals forces, enhancing the adhesion between the PP fibers and CSH and reducing interfacial defects. The specific steps for preparing the NS-modified PP cement-based repair material in the experiment are as follows: Step 1: PP Fiber Pretreatment. Place 6mm long PP fibers in deionized water for ultrasonic cleaning at a frequency of 40kHz for 5-10 minutes to remove surface dust, oil, and other impurities. After ultrasonic cleaning, remove the PP fibers, absorb excess moisture with filter paper, and dry at a low temperature (50-80°C) for later use.

[0031] Step 2: NS Pretreatment. NS is added to deionized water, and a polycarboxylate superplasticizer is added as a dispersant at a concentration of 0.5% of the solution mass. The NS suspension is then treated with ultrasonic dispersion at a frequency of 40 kHz, a power of 0.1-0.3 W / mL, and a treatment time of 5-15 min, to ensure uniform dispersion of NS in the water, forming a 10% NS dispersion.

[0032] Step 3: Preparation of the silane coupling agent treatment solution. Add silane coupling agent KH-550 to a mixed solution of deionized water and ethanol, and adjust the pH of the solution to 4.5-5.5 using glacial acetic acid. The amount of silane coupling agent added is 1% of the solution mass. Stir continuously at room temperature for 30-60 minutes to ensure complete hydrolysis of the silane coupling agent, obtaining the silane coupling agent treatment solution.

[0033] Step 4: Hydrophilic modification of PP fiber surface. Place the PP fibers pretreated in Step 1 into the silane coupling agent treatment solution obtained in Step 3, and gently stir at room temperature for 30-60 minutes to allow the silane coupling agent molecules to adhere to the PP fiber surface. After treatment, remove the PP fibers, absorb excess treatment solution with filter paper to keep the fibers moist but not dripping, and then dry them at a low temperature (50-80°C) for later use.

[0034] Step 5: Composite modification of PP fibers with NS. PP fibers treated with silane coupling agent are added to the NS dispersion obtained in Step 2, where the mass ratio of NS to PP fibers is 5:1. Composite treatment is performed using low-power pulsed ultrasound at a frequency of 40 kHz, a power of 0.1-0.3 W / mL, and a treatment time of 5-15 min. Through ultrasonic dispersion and physical stirring, NS is uniformly adhered to the surface of the PP fibers, resulting in NS-modified PP fibers.

[0035] Step 6: Drying the modified PP fibers. The NS-modified PP fibers obtained in Step 5 are dried at a low temperature of 50-80℃ to remove residual moisture from the fiber surface. During the drying process, avoid excessively high temperatures that could deform the PP fibers or damage the modified layer. After drying, NS-modified PP fibers suitable for use in cement-based repair materials are obtained.

[0036] Step 7: Wet pre-dispersion. Add NS-modified PP fibers to water containing polycarboxylate superplasticizer at a volume ratio of 0.5 vol%, and pre-disperde using mechanical stirring. Add the fibers slowly during stirring to avoid agglomeration caused by adding them all at once. After stirring, a uniformly dispersed fiber pre-dispersion slurry is obtained.

[0037] Step 8: Preparation of cement-based repair material. Slowly add the fiber pre-dispersed slurry obtained in Step 7 to the cement slurry while stirring, ensuring the NS-modified PP fibers are evenly distributed in the cement slurry. Adjust the water content or water-reducing agent dosage appropriately according to the slurry's fluidity to achieve suitable fluidity, injectability, and filling properties in the resulting repair material. The final product is an NS-modified PP fiber cement-based repair material for repairing cracks in ancient building brick and stone structures. (Refer to...) Figure 1 .

[0038] Combination Figure 4 The application of a cement-based repair material based on NS-modified PP fiber in the repair of cracks in ancient building brick and stone structures, with the specific construction steps as follows: S1. Low-Damage Cleaning of Cracked Areas. Before construction, the cracked areas of the ancient building's brick and stone structure are first inspected to determine the width, depth, and extent of loose material. A small, soft brush is used to remove surface dust, loose particles, and flaking material from the cracks, and a low-powered vacuum cleaner is used to remove dust from inside the cracks. During the cleaning process, strong washing, hammering, or high-pressure gas should not be used to avoid secondary damage to the original brick and stone materials.

[0039] S2. Interface Wetting and Bonding Layer Treatment. After the cracks are cleaned, the surface and inner walls of the cracks are lightly moistened, ensuring the old brick and stone substrate is surface-moist but without visible water. Then, a layer of cement slurry with the same mix ratio as the repair material is applied as an interface bonding layer, creating a transition interface between the old and new materials and improving the adhesion between the repair material and the original brick and stone structure.

[0040] S3. Crack Injection Filling. After the initial adhesion of the interface bonding layer, the NS-modified PP fiber cement-based repair material is slowly injected into the crack using a low-flow injection method. Injection should begin from the deeper or lower part of the crack and gradually proceed outwards or upwards, ensuring the repair material fully fills the crack voids. Avoid high-pressure injection in one go to minimize disturbance to the original masonry structure.

[0041] More preferably, for cracks that are wider or deeper, a layered filling method should be used. After each layer of repair material is filled, it should be gently compacted using a small trowel to ensure full contact between the material and the inner wall of the crack, while avoiding excessive force that could damage the edges of the old brickwork. Once the previous layer has stabilized, the next layer can be applied until the crack is completely filled.

[0042] S4. Surface Smoothing and Fiber Covering Treatment. After the crack filling is completed, the surface of the repaired area is slightly smoothed to make the surface of the repair material basically flush with the surface of the surrounding brickwork. If there are a small amount of exposed PP fibers on the surface, a thin layer of cement slurry with the same mix ratio is applied to cover the exposed fibers and improve the surface appearance.

[0043] S5. Antique Surface Treatment. After the restoration material has reached a preliminary hardened state, a surface treatment material with a color similar to that of the surrounding ancient building bricks and stones is applied to the restoration surface. This ensures that the restored area is coordinated with the surrounding original materials in terms of color, texture, and roughness, thereby reducing the impact of restoration marks on the overall appearance of the ancient building.

[0044] S6. Curing. After the repair is completed, the repaired area should be properly cured to keep the surface moist and prevent early water loss and cracking. During the curing period, external disturbance, rain erosion, and strong sunlight should be avoided to ensure that the repair material is fully hydrated and forms a stable interface bond.

[0045] Working principle: Combination Figure 2-3 By comparing the stress-strain and fracture energy of the CSH / PPNS model with those of CSH, the initial stress increase trends of both CSH and CSH / PPNS are similar. However, at higher strains, CSH / PPNS exhibits a more gradual decrease, suggesting that the addition of PPNS allows the material to maintain high strength even under significant deformation. CSH, after reaching its peak, decreases rapidly, indicating that it may exhibit relatively small plastic deformation before fracture. In contrast, the CSH / PPNS curve shows a gentler decrease, demonstrating better ductility. The addition of PPNS significantly increases the fracture energy, substantially improving the material's tensile strength. The purpose of the fatigue test is to investigate the material's performance under multiple earthquakes.

[0046] As the number of fatigue cycles increases, the stress and strain amplitudes of the CSH material gradually decrease, indicating that the material is gradually entering a fatigue state. In contrast, the CSH / PPNS curves are more stable, and even after 200 cycles, the material still maintains a relatively large stress and strain amplitude. This suggests that the addition of PPNS increases the material's fatigue resistance and slows down the performance degradation caused by fatigue cycles.

[0047] Figure 2 and Figure 3 The results indicate that NS-modified PP fibers do not simply improve the instantaneous strength of the material, but rather transform cement-based repair materials from brittle to ductile failure by improving the fiber-matrix interface, enhancing crack bridging, and increasing energy dissipation. This performance improvement is significant for the repair of cracks in ancient brick and stone structures. On the one hand, the material can maintain a certain residual load-bearing capacity during crack propagation, reducing the risk of sudden cracking or spalling of the repair layer; on the other hand, the material exhibits good fatigue stability under repeated seismic loading, which is beneficial for improving the long-term durability and seismic adaptability of the repaired area.

[0048] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.

Claims

1. A method for preparing a cement-based repair material based on NS-modified PP fibers, characterized in that, Includes the following steps: Step 1: Pre-treat the PP fibers to remove surface impurities; Step 2: Pre-treat the NS to obtain an NS dispersion with a mass fraction of 8% to 12%; Step 3: Prepare the silane coupling agent treatment solution; Step 4: Place the pretreated PP fiber in a silane coupling agent treatment solution to modify the surface of the PP fiber to be hydrophilic. Step 5: Add the hydrophilically modified PP fibers to the NS dispersion to make the NS evenly adhere to the surface of the PP fibers. Step 6: Obtain NS-modified PP fibers by low-temperature drying; Step 7: Add NS modified PP fiber to water containing polycarboxylate superplasticizer at a volume dosage of 0.5 vol% to achieve wet pre-dispersion and obtain a uniformly dispersed fiber pre-dispersion slurry. Step 8: Add the fiber pre-dispersed slurry to the cement material to obtain NS modified PP fiber cement-based repair material for repairing cracks in masonry structures.

2. The preparation method of a cement-based repair material based on NS-modified PP fiber according to claim 1, characterized in that, In step 1, the PP fiber is placed in deionized water for ultrasonic cleaning to remove floating dust, oil and other impurities from the surface of the PP fiber.

3. The method for preparing a cement-based repair material based on NS-modified PP fiber according to claim 1, characterized in that, Preparation of NS dispersion: NS is added to deionized water, and polycarboxylate superplasticizer is added as a dispersant. The amount of polycarboxylate superplasticizer is 0.5% of the solution mass. The NS is uniformly dispersed in water by ultrasonic dispersion.

4. The method for preparing a cement-based repair material based on NS-modified PP fiber according to claim 1, characterized in that, Add silane coupling agent KH-550 to a mixed solution of deionized water and ethanol, and adjust the pH of the solution to 4.5-5.5 using glacial acetic acid; the amount of silane coupling agent added is 1% of the solution mass; stir continuously at room temperature for 30-60 minutes to allow the silane coupling agent to be fully hydrolyzed, and obtain the silane coupling agent treated solution.

5. The method for preparing a cement-based repair material based on NS-modified PP fiber according to claim 1, characterized in that, NS dispersion and PP fiber are prepared at a mass ratio of 5:1, and ultrasonic dispersion and physical stirring are used to make NS uniformly adhere to the surface of PP fiber to obtain NS modified PP fiber.

6. The method for preparing a cement-based repair material based on NS-modified PP fiber according to claim 1, characterized in that, NS-modified PP fibers are dried at a low temperature of 50-80℃.

7. A method for repairing cracks in the brick and stone structure of ancient buildings, characterized in that, The repair steps are as follows: S1. Clean the dust from the cracked area; S2. Wet the surface and inner wall of the crack, and then apply a layer of cement slurry with the same ratio as the repair material as the interface bonding layer. S3. After the interface bonding layer is initially attached, the NS modified PP fiber cement-based repair material prepared by the cement-based repair material based on NS modified PP fiber as described in claim 1 is slowly injected into the crack. S4. After the crack is filled, the surface of the repaired area is lightly smoothed. S5. After the material to be repaired reaches a preliminary hardening state, perform an antique-style surface treatment on the repair surface. S6. Perform maintenance on the repaired area.

8. A method for repairing cracks in the brick and stone structure of ancient buildings according to claim 7, characterized in that, During injection, start from the deeper or lower part of the crack and gradually move outward or upward to ensure that the repair material fully fills the crack gaps.

9. A method for repairing cracks in the brick and stone structure of ancient buildings according to claim 7, characterized in that, A layered filling method is adopted, that is, after each layer of repair material is filled, it is compacted; after the previous layer has initially stabilized, the next layer is filled.